Impact of internal migration movements on the schooling process in Turkey: Supervisors’ views - Akar, Hanife; Şen, Derya (Education Policy Analysis Archives, 2017)
This study attempted to examine the impact of interregional and urban–rural population movements on schools located in areas subjected to high in-migration and out-migration flows in Turkey based on data collected from primary school supervisors (N=150). A cross-sectional survey design was utilized to examine the most pressing problems confronted in those schools, and possible actions that could be taken by various stakeholders were sought. Overall data suggest that those schools serve mostly disadvantaged populations with poor households. Among the main challenges revealed are lack of adequate school resources and poor facilities, problems caused due to ineffective and untimely implementation of the program, high personnel turnover and recruitment of largely inexperienced and relatively less qualified educational staff, and lower levels of parental involvement in children’s schooling. Accordingly, proposed recommendations focused on measures to eliminate capacity and resource constraints, improve hiring practices, and secure adequate supervision and support for educational staff, meet academic and socio-emotional needs of students and facilitate parental involvement in the education of children.